Beneficial effects of fermented jujube pulp in relieving loperamide hydrochloride-induced constipation in male ICR mice - Jing Li; Xinyue Yu; Xinxing Xu; Peipei Tang; Shuang Bi; Xiaopu Ren; Yong Shi; Jihong Wu; Fei Lao (Food Science and Human Wellness)
Unfermented jujube pulp (UFJP), fermented jujube pulp (FJP) in high and low doses were fed to constipated ICR mice. Defecation function, serum gastrointestinal regulatory peptide, fecal short-chain fatty acids (SCFAs) and gut microbial composition were assessed. Results showed that high-dose FJP could protect intestinal mucosa tissue, shorten the first black feces defecating time by 17 % and increase the number and wet weights of black feces by 72 % and 71 %, respectively, within 6 h. High-dose FJP significantly down-regulated the somatostatin level and up-regulated gastrin level in constipated mice, compared with low-dose FJP and UFJP. High-dose FJP intervention regulated the microbiota profile, which afterwards restored microbiota, like Bacteroidetes, Bifidobacterium and Lactobacillus, to a less unhealthy state. This study provides convincing in vivo evidence that high-dose FJP supplementation through daily diet could be a promising approach to effectively alleviate constipation and modulate gut health.